2001
DOI: 10.1021/jp011815c
|View full text |Cite
|
Sign up to set email alerts
|

Nanocrystal Arrested Precipitation in Supercritical Carbon Dioxide

Abstract: Fluorocarbon-coated silver, iridium, and platinum nanocrystals ranging in size from 20 to 120 Å in diameter are synthesized in supercritical (sc)-CO2 by arrested precipitation from soluble organometallic precursors. The synthesis is performed in a single CO2 phase by reduction with H2 at elevated temperatures ranging from 60 to 100 °C. Precursor degradation and particle nucleation occur in the presence of stabilizing perfluorooctanethiol ligands, which bind to the surface of the metal agglomerates and quench p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
118
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(129 citation statements)
references
References 40 publications
7
118
2
Order By: Relevance
“…It has been demonstrated that hydrocarbon ligands provide some degree of steric stabilization in the formation of nanocrystals in sc-CO 2 . [32] The repulsive forces of the surface passivated nanoparticles are determined by the surface coverage of the capping ligands, the length of the ligand tail and the solvent quality. [19] In the context of this study, a poor solvent such as sc-CO 2 would cause the ligand tails to collapse partially, augmenting the overall attractive forces and increasing the aggregation of nuclei during the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…It has been demonstrated that hydrocarbon ligands provide some degree of steric stabilization in the formation of nanocrystals in sc-CO 2 . [32] The repulsive forces of the surface passivated nanoparticles are determined by the surface coverage of the capping ligands, the length of the ligand tail and the solvent quality. [19] In the context of this study, a poor solvent such as sc-CO 2 would cause the ligand tails to collapse partially, augmenting the overall attractive forces and increasing the aggregation of nuclei during the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent approach, a sonochemical method was used to diffuse the nanoparticle through the solvent inside the pores of the mesoporous material, which was undesirably slow due to the low diffusivity of the medium. [14] The potential use of supercritical carbon dioxide (scCO 2 ) has attracted much interest as a sustainable and "green" medium for material synthesis. It can be handled easily because it is non-toxic, non-flammable and inexpensive.…”
Section: Introductionmentioning
confidence: 99%
“…Supercritical CO 2 also proved to be a good solvent for fluorous nanoparticles synthesis by using suitable organometallic precursors and hydrogen as reducing agent [21,22].…”
Section: "Perfluorinated" Gold Nanoparticlesmentioning
confidence: 99%